Variations in dynamic tumor-associated antigen-specific T cell responses correlate with HCC recurrence after thermal ablation - Zang, Chaoran; Zhao, Yan; Liu, Guihai; Li, Kang; Qin, Ling; Zhang, Yuewei; Sun, Jianping; Wang, Qi; Ma, Liang; Zhao, Peng; Sun, Yu; Guo, Dandan; et al. (Frontiers in Immunology, 2022)
Introduction: Ablation has been a recommended treatment for hepatocellular carcinoma (HCC) not only for its destruction for tumours but also for its induction of host immunity. However, the high 5-year recurrence rate after ablation indicates the insufficient understanding of antitumor immunity. Here we investigated the effect of thermal ablation on anti-tumour immunity. Methods: We analysed the dynamic of tumor-associated-antigen (TAA) specific immune responses and the change of phenotypes in peripheral blood of HCC before and after ablation using IFN-γ ELISPOT assay and flowcytometry to identify the role of ablation to host immunity. Then, the correlation between T cell response and disease outcome was explored to uncover the effect of immune response to inhibit HCC recurrence. Results: Distinct TAA-specific T cell responses were found between patients before and after ablation. One week after ablation, it was with an improved immune status, from AFP-specific T cell response dominance to SMNMS-specific T cell response dominance. This transformation correlated with a better survival. Moreover, the demonstrated improved immune status was accompanied by less PD1 and Tim3 expression. While this functional state was not durable, with more appearance of AFP-specific T cell response at 4 weeks after ablation. Meanwhile, T cells were with a more exhausted phenotype at 4 weeks after ablation compared with that of 1 week in these patients. Conclusions: Ablation could evoke a transient anti-tumour immune in HCC patients by changing the T cell response profile and the expression of immune checkpoint, which correlated with a longer HCC recurrence-free survival.